2020
DOI: 10.1101/2020.03.19.20033175
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of patients with COVID-19 during epidemic ongoing outbreak in Wuhan, China

Abstract: Background Since Dec 2019, SARS-CoV-2 has caused about fifty thousand patients and over two thousand deaths in Wuhan, China. We reported characteristics of patients with COVID-19 during epidemic ongoing outbreak in Wuhan.Methods Data of COVID-19 patients with clinical outcome in a designated hospital in Wuhan, were retrospectively collected from electronic medical records. Characteristics were compared between patients who died or recovered, and between patients with different disease severity.Results By Feb 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 17 publications
2
57
0
1
Order By: Relevance
“…30 studies were included in the qualitative synthesis and meta-analysis [ Figure 1]. [3,8,[17][18][19][20][21][22][23][24][25][26]9,[27][28][29][30][31][32][33][34][35][36][10][11][12][13][14][15][16] There were a total of 6452 patients from 30 studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…30 studies were included in the qualitative synthesis and meta-analysis [ Figure 1]. [3,8,[17][18][19][20][21][22][23][24][25][26]9,[27][28][29][30][31][32][33][34][35][36][10][11][12][13][14][15][16] There were a total of 6452 patients from 30 studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…1). Overall, there were six cohort studies [11,[14][15][16][17][18] and two case series [19,20] comparing on-admission D-dimer levels between non-survivors and survivors, and one cohort study [12] comparing patients with elevated D-dimer levels and normal D-dimer levels on admission. Only two studies were prospective studies [14,18], while the others were retrospective in nature.…”
Section: Search Selection and Quality Assessmentmentioning
confidence: 99%
“…Only two studies were prospective studies [14,18], while the others were retrospective in nature. All studies were conducted in China [11,12,[14][15][16][17]19], except for two studies carried out in the USA [20] and Italy [18], respectively. The quality and risk of bias assessment of the included studies are shown in Tables S3 and S4.…”
Section: Search Selection and Quality Assessmentmentioning
confidence: 99%
“…Epidemiological studies have identified several demographic features that correlate with the severity of clinical COVID-19 cases. While fewer than 5% of SARS-CoV-2 infections are fatal 10 , men and elderly patients are particularly at risk of developing severe disease 11–14 . Additionally, cigarette smokers are highly susceptible to SARS-CoV-2 and are significantly more likely to require aggressive clinical interventions: in a study of 1,099 patients with laboratory-confirmed COVID-19, 12.3% of current smokers required mechanical ventilation, were admitted to an ICU, or died, compared to only 4.7% of non-smokers 12 .…”
Section: Introductionmentioning
confidence: 99%